Historical biogeography of the widespread macroalga Sargassum (Fucales, Phaeophyceae) - Yip, Zhi Ting; Quek, Randolph Z. B.; Huang, Danwei; Smith, J. (Journal of phycology, 2020)
Sargassum is a cosmopolitan brown algal genus spanning the three ocean basins of the Atlantic, Pacific and Indian Oceans, inhabiting temperate, subtropical and tropical habitats. Sargassum has been postulated to have originated in the Oligocene epoch approximately 30 mya according to a broad phylogenetic analysis of brown macroalgae, but its diversification to become one of the most widespread and speciose macroalgal genera remains unclear. Here, we present a Bayesian molecular clock study, which analyzed data from the order Fucales of the brown algal crown radiation (BACR) group to reconstruct a time‐calibrated phylogeny of the Sargassum clade. Our phylogeny included a total of 120 taxa with 99 Sargassum species sampled for three molecular markers – ITS‐2, cox3 and rbcLS – calibrated with an unambiguous Sargassaceae fossil from between the lower and middle Miocene. The analysis revealed a much later origin of Sargassum than expected at about 6.7 mya, with the genus diversifying since approximately 4.3 mya. Current geographic distributions of Sargassum species were then analyzed in conjunction with the time‐calibrated phylogeny using the dispersal‐extinction‐cladogenesis (DEC) model to estimate ancestral ranges of clades in the genus. Results strongly support origination of Sargassum in the Central Indo‐Pacific (CIP) region with subsequent independent dispersal events into other marine realms. The longer history of diversification in the ancestral CIP range could explain the much greater diversity there relative to other marine areas today. Analyses of these dynamic processes, when fine‐tuned to a higher spatial resolution, enable the identification of evolutionary hotspots and provide insights into long‐term dispersal patterns.